Replication origin region of Bacillus subtilis chromosome contains two rRNA operons. - Ogasawara, N (1983)
The first replicating DNA fragment (BamHI-7) of the Bacillus subtilis chromosome contains two promoters for a rRNA operon. A map of restriction enzyme cleavage sites of the region of replication origin suggests the presence of a second rRNA operon in this region. Hybridization of rRNA genes (rDNA) with DNA fragments derived from the origin region by treatment with various enzymes clearly revealed two rRNA operons in this region, one at the B7-B3 junction and the other at the B5-B6 junction. The restriction enzyme cleavage sites surrounding the rRNA operons show that the operon at the B5-B6 junction corresponds to the rrnA operon. A novel operon at the B7-B3 junction was termed rrnO. Transformation by density-labeled fragments of the origin region showed that the first replicating marker, guaA, is located in the B3 fragment. From these results, a map was constructed for the first time to correlate the genetic markers with the physical structure of the replication origin region of the B. subtilis chromosome. The role of the rrnO operon in regulating the initiation of chromosomal replication is discussed, based on the fact that the promoter of the rrnO operon suppresses the replication of the plasmid carrying the promoter.